Anti-inflammation effect of Apium graveolens Extract against lead-acetate-induced brain injury in rats - Sulistyo, Sona; Sarosa, Hadi; Sumarawati, Titiek; Putra, Agung; Chodidjah, Chodidjah; Amalina, Nur Dina; Ibrahim, Sugeng (International Journal of Cell and Biomedical Science, 2023)
Purpose: The current study investigated the protective potential of Apium graveolens extract (APE) against lead-induced brain injury in rats by exploring anti-inflammatory and antiapoptotic mechanism. Methods: Twenty male Wistar rats were randomly allocated into four groups (n=5). The control group was orally administrated with distillate water. The second group received lead acetate 200mg/kg body weight orally for 14 days, the third group were orally administered lead acetate 200 mg lead acetate/kg body weight and vitamin E 50IU/kg body weight for 14 days. The fourth group was administrated with leas acetate like second group and APE 300mg/kg body weight for 14 days. The TNF-a levels and caspase-3 expression was analyses under ELISA and flow cytometry assay, respectively. Results: The phytochemical analysis of APE indicated the presence of alkaloids, flavonoids, tannins, saponins, and steroids. Leads acetate increased the serum levels of TNF-α and caspase-3 expression, as well as altering the brain tissue architecture. Conclusion: In conclusion, the presence of APE inhibited the lead acetate toxicity by inhibition of TNF-α proinflammation protein and caspase-3 proapoptosis protein.